Spatial analysis of speculation in the US housing market - Salaheddin Manochehri; Ramin Amani; Jamal Mamkhezri (Future Business Journal)
Abstract This study examines the spatial impact of speculation on the US housing market from 1990 to 2021, highlighting regional variations and economic implications. Employing advanced analytical techniques, including nonlinear least squares and time-varying parameter ordinary least squares, we delve into the spatial patterns of speculation within the housing market. This study aims to illuminate the role of speculation in influencing housing market dynamics, which has significant implications for economic stability and housing policy. Our investigation reveals that speculation is primarily driven by price expectations and historical price trend analysis, exerting a significant influence on housing market dynamics. Given the inherent constraints in housing supply, effectively managing these fluctuations necessitates a multifaceted strategy. This approach involves measures such as accelerating production, streamlining supply chains, and facilitating affordable land access and tax incentives for low-income households, all designed to stimulate investment in construction and housing. Our empirical findings indicate variations in speculation prevalence across different regions of the USA, with a higher incidence in the western and midwestern regions compared to the eastern counterparts. In light of these insights, policymakers are urged to consider tailored regulatory interventions to mitigate excessive speculation in the US housing market. These measures could encompass stricter lending standards and enhanced transparency requirements in real estate transactions. This study contributes to a deeper understanding of the dynamics of speculation within the US housing market, offering valuable insights for policymakers and researchers seeking to address its implications for economic stability. Moreover, Our findings not only highlight regional variations but also validate theories of speculative behavior, particularly the role of price expectations and feedback loops, as established by Shiller (2005) and Glaeser (2013). These insights contribute to a deeper understanding of the dynamics driving speculation in the housing market.